2023
DOI: 10.3390/su15065603
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Neurodiversity in Physical Education Lessons: A Sustainable and Inclusive Challenge for Teachers

Abstract: Attentional neurodiversity is evidenced in the majority of current schools. The role that physical education plays for the inclusion of students with attentional problems in the school is quite relevant. This essay aims to show the effectiveness of sports and physical exercise on the core symptoms of schoolchildren and adolescents with attention deficit/hyperactivity disorder (ADHD). What is more, this proposal sheds light the key differences between clinical conditions of physical exercise and/or sport interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In physical education teaching, from immediate, short-term events to distant, long-term events, both teachers and students have relevant factors that lead to an active lifestyle for adolescents [11]. In addition, studies have shown that physical education can also improve attention problems in children and adolescents [12]. With the acceleration of the educational information process, the management and integration of college sports resources through cloud computing can promote the mutual exchange of college resources and have practical significance for the development of college education [13].…”
Section: Introductionmentioning
confidence: 99%
“…In physical education teaching, from immediate, short-term events to distant, long-term events, both teachers and students have relevant factors that lead to an active lifestyle for adolescents [11]. In addition, studies have shown that physical education can also improve attention problems in children and adolescents [12]. With the acceleration of the educational information process, the management and integration of college sports resources through cloud computing can promote the mutual exchange of college resources and have practical significance for the development of college education [13].…”
Section: Introductionmentioning
confidence: 99%